Complete genome analysis of the African swine fever virus genotypes II and IX responsible for the 2021 and 2023 outbreaks in Rwanda - Hakizimana, Jean Nepomuscene; Yona, Clara; Makange, Mariam Richard; Adamson, Ester Kasisi; Ntampaka, Pie; Uwibambe, Evodie; Gasana, Method Ngabo; Ndayisenga, Fabrice; Nauwynck, Hans; Misinzo, Gerald (Frontiers in Veterinary Science, 2025)
African swine fever (ASF) is a devastating viral hemorrhagic disease caused by the ASF virus (ASFV) that can kill up to 100% of domestic pigs and wild boars. The domestic pig industry in Rwanda is highly threatened by ASF, with several outbreaks reported yearly to the World Organization for Animal Health. Despite the endemic status, no ASFV from Rwanda has been genetically characterized. This study reports, for the first time, the ASFV genotypes causing outbreaks in Rwanda. The ASF confirmation was performed by polymerase chain reaction followed by molecular characterization of the causative ASFV by partial and complete genome sequencing and phylogenetic reconstruction. After genetic analysis, the ASFV strains responsible for the 2021 outbreak in eastern Rwanda clustered within genotype II, while the strain from the 2023 outbreak in northern Rwanda clustered within genotype IX. The extension of the geographical range of genotype II in eastern Africa is of concern. In the countries of the East African Community, this ASFV genotype was reported for the first time in Tanzania at the Tanzania-Malawi border in 2011, followed by a relentless spread of the virus northwards along major highways within Tanzania before the detection of this genotype in Rwanda in 2021. This ASFV genotype will most likely reach other eastern African countries threatening the regional domestic pig industry. The ongoing spread of ASFV genotypes II and IX across Africa impacts food and nutritional security, and hinders the realization of the United Nations Sustainable Development Goal 1 (No Poverty) and·Goal 2 (Zero hunger). The results of this study call for science-driven and regional approaches to enable the timely identification of ASF outbreaks for effective prevention and containment.